1991
DOI: 10.3139/217.910332
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Mechanical Property Development in the Melt Spinning of Fibers from Polyetherimide and Polyarylate

Abstract: An experimental study of structure development in melt spinning polyetherimide (PEI) and polyarylate (PAR) is presented. PEI was melt spun at 320° and 350°C and PAR at 310° and 340°C to drawdown ratios of up to 1 000. The melt spun fibers were found to be totally amorphous but to have significant levels of birefringence which increased with draw-down ratio. The birefringence was found to vary linearly with the spinline stress for both polymers and the data was independent of the melt spinning temperature. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Drawing-induced orientation in an amorphous filament has also been reported for PEI by Song et al , who observed that birefringence increased linearly with the degree of drawing [9]. For the equatorial scattering, which can be attributed to the chain segments oriented parallel to the fiber direction [28], a preferential interchain distance of 5.3 Å can be calculated from the maximum of the fitted peak at 7.7° 2 θ .…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Drawing-induced orientation in an amorphous filament has also been reported for PEI by Song et al , who observed that birefringence increased linearly with the degree of drawing [9]. For the equatorial scattering, which can be attributed to the chain segments oriented parallel to the fiber direction [28], a preferential interchain distance of 5.3 Å can be calculated from the maximum of the fitted peak at 7.7° 2 θ .…”
Section: Resultsmentioning
confidence: 56%
“…Some of the initial literature reports on melt spinning of amorphous materials refer to the high performance polyetherimide (PEI) polymer. Having a predominantly aromatic structure, PEI is reported by Song et al to remain completely amorphous even after substantial drawing, resulting in filaments with a tensile strength of 800 MPa, strain to break of 40% and Young’s modulus of 5.5 GPa [9]. In contrast, attempts to melt-spin the highly aromatic poly (arylene ether sulfone) using a capillary rheometer and take-up roller resulted in filaments which remained amorphous under all processing conditions while reaching a tensile strength of 350 MPA and Young’s modulus of 3.5 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…In the stress-strain curve of PEI filament at a cooling temperature of 200 C, it was confirmed that elongation increased and yield strength and break force decreased significantly. 24,25 Therefore, to optimize the mechanical properties of the filament through the thermal stretching process, the cooling temperature needs to be optimized such that the crystalline regions of PEI filament remain unaffected.…”
Section: Resultsmentioning
confidence: 99%